Cardiovascular autonomic and peripheral sensory neuropathy in women with obesity - Keller, Nóra; Zádori, János; Lippai, Balázs; Szöllősi, Dalma; Márton, Virág; Wellinger, Károly; Lada, Szilvia; Szűcs, Mónika; Menyhárt, Adrienn; Kempler, Péter; Baczkó, István; Várkonyi, Tamás; et al. (Frontiers in Endocrinology, 2024)
Introduction: A higher incidence of neural dysfunction in people with obesity has been described. We determined the prevalence of neuropathic lesions in obese women and evaluated their potential association with anthropometric and laboratory parameters.In our cross-sectional study, we enrolled female patients with obesity and without diabetes before obesity treatment. Voluntary female subjects were controls with a normal body mass index (BMI). Autonomic function was assessed by Ewing's cardiovascular reflex tests, while comprehensive peripheral neuropathic assessments were conducted utilizing the Neurometer®, Tiptherm®, Monofilament®, and Rydel-Seiffer tuning fork tests. Sudomotor function was assessed by the Neuropad®-test. Body composition was examined using the InBody 770.Results: 71 patients (mean ± SD; age: 36.1±8.3 years; BMI: 40.2±8.5 kg/m 2 ) and 36 controls (age: 36.4±13.3 years; BMI: 21.6±2.1 kg/m 2 ) were enrolled. Patients had significantly higher systolic (patients vs. controls; 137.5±16.9 vs. 114.6±14.8 mmHg, p<0.001) and diastolic (83.0±11.7 vs.69.8±11.2 mmHg, p<0.001) blood pressure compared to controls. Among autonomic tests, only the heart rate response to Valsalva maneuver (Valsalva-ratio) revealed significant impairment in patients (1.4±0.2 vs. 1.7±0.4, p<0.001). Neurometer® at the median nerve revealed increased current perception threshold (CPT) values at all stimulating frequencies in patients (CPT